Guidelines ARRIVE review, in chilean scientific journal articles, indexed in Thomson Reuters, that use animal experimentation, in vivo, between years 2010 and 2012 - Galindo, Leslie; Troncoso, Ignacio; Ureña, Diana; Jiménez, Eliana; Luzio, Álvaro (Acta Bioethica, 2015)
We propose to know the national situation regarding scientific publishing using experimental animals, based on the guidelines ARRIVE (Animal Research: Reporting In Vivo Experiments) for animal research. It aims to evaluate the methodology of a clinical trial, from the detailed description, with accuracy and transparency, its design, execution, analysis and results. They selected six Chilean magazines, that use experimental animals and belong to the biomedical sciences, since January 2010, when it was published ARRIVE regulations, to December 2012. Corresponding to 12.2% (6/49) of total Chilean journals indexed in Thomson Reuters. Of these 110 articles were selected, from a total of 1567, corresponding to 7%. Of the articles analyzed, none fulfilled with the total ARRIVE regulation parameters for use of experimental animals. Challenges arise for scientific research that uses animals for research, as well as for those journals that disseminate information obtained from these investigations. With the purpose of increasing the quantity and quality of these publications.